2015
DOI: 10.18805/lr.v0iof.6848
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of berseem (<italic>Trifolium alexandrinum</italic> L.) rhizobia isolated from Haryana soil

Abstract: Total of forty rhizobia were isolated from nodule samples of berseem crop from farmers' fields representing 17 villages of Haryana state, India. All the isolates were Gram-negative small rods and authenticated as rhizobia by plant infectivity test. Twenty nine rhizobial isolates on the basis of good nodulation characteristics were further selected for molecular diversity study. The amplified PCR product of genomic DNA of all the 29 rhizobia was digested with HaeIII restriction enzyme which resulted in polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Several Rhizobium isolates of pigeon pea, chickpea and soybean in acid soils analyzed by proteomic tools, which showed unique protein differences amongst acid-soil tolerant isolates (Dubey et al, 2016 ). Garg et al (2016) found seven biotypes of `berseem' rhizobia in Haryana soils of which two types were common in three districts showing some degree of endemism even in the high temperature arid soils.…”
Section: Rhizobial Diversitymentioning
confidence: 99%
“…Several Rhizobium isolates of pigeon pea, chickpea and soybean in acid soils analyzed by proteomic tools, which showed unique protein differences amongst acid-soil tolerant isolates (Dubey et al, 2016 ). Garg et al (2016) found seven biotypes of `berseem' rhizobia in Haryana soils of which two types were common in three districts showing some degree of endemism even in the high temperature arid soils.…”
Section: Rhizobial Diversitymentioning
confidence: 99%
“…Previous studies showed that the different legumes in arid zone harbour widely diverse and promiscuous rhizobia residing in nodule endosphere as well as rhizospheric soil (Zahran, 2001). Although different legumes belong to same family there is enormous diversity found among rhizobial community around rhizospheric soil and nodule endosphere (Wadhwa et al 2011;Garg et al 2016). There are various literature found on the diversity of legume rhizobia nodulating different beans but they belong to rhizobial diversity of nodule endosphere or for comparison with R. leguminosarum strains isolated from other legume species (Dudeja et al 2012) or inhabiting in rhizospheric soil (Gera et al 2013), but no significant information is available on the diversity and phylogeny of abiotic stresstolerant rhizobia isolated from clusterbean grown under extreme environmental conditions of hyper-arid zone of India.…”
Section: Introductionmentioning
confidence: 99%